The Bobbsey twins' wonderful winter secret - Hope, Laura Lee. (New York Grosset & Dunlap, 1962)
When the Bobbsey twins ponder the perfect Christmas gift for Mother and Father, they decide upon Project Santa Claus.
Keywords: Christmas -- Fiction